2020
DOI: 10.1038/s41598-020-71035-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of high-activity cytochrome P450 in mammalian cells

Abstract: The evaluation of Cytochrome P450 (CYP) enzymatic activity is essential to estimate drug pharmacokinetics. Numerous CYP allelic variants have been identified; the functional characterisation of these variants is required for their application in precision medicine. Results from heterologous expression systems using mammalian cells can be integrated in in vivo studies; however, other systems such as E. coli, bacteria, yeast, and baculoviruses are generally used owing to the difficulty in expressing high CYP lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 37 publications
(62 reference statements)
1
26
0
Order By: Relevance
“…The protein expression was low at 24 hours, peak at 48 hours and reduced at 72 hours post-transfection. This finding is consistent with a recent study which reported that 48 hours incubation period post-transfection was necessary to obtain saturated CYP isozymes expression levels [3]. shown no alteration in morphology in comparison to control cell without transfection.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The protein expression was low at 24 hours, peak at 48 hours and reduced at 72 hours post-transfection. This finding is consistent with a recent study which reported that 48 hours incubation period post-transfection was necessary to obtain saturated CYP isozymes expression levels [3]. shown no alteration in morphology in comparison to control cell without transfection.…”
Section: Resultssupporting
confidence: 93%
“…6, jet PRIME® has resulted in higher transfection efficiency in comparison to Although jetPRIME® was proven to have higher transfection efficiency, the efficiency of lower cost PEI is sufficient in overexpressing CYP2C9 without significant toxicity for the purpose of further development of an in vitro based cell model. The use of commercial jet PRIME® transfection reagent would be bene for the purpose of purification of the overexpressed enzyme or microsome preparation for downstream application such as demonstrated in previous study [3], where toxicity does not affect the cell-free enzymatic assay. In contrast, significant transf mediated toxicity can adversely affect experimental results of cell assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gutierrez Rico et al, 2020;Kumondai et al, 2018;Lee et al, 2005;Maekawa et al, 2010;Saito et al, 2018;Watanabe et al, 2018 DMD-AR-2020-000261 10 intronic CYP2D6 mutation was evaluated using a mini-gene expression system with transfected whole CYP2D6 sequences (<5 kb) (Zanger et al, 2020). Mini-genes may aid the assessment of CYP3A4 levels.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Therefore, we used our heterologous expression system consisting of 293FT cells co-expressing CYP3A4, cytochrome P450 oxidoreductase (CPR), and cytochrome b 5 (Kumondai et al, 2020).…”
Section: Downloaded Frommentioning
confidence: 99%